Improving Language Skills Through Linguistic Intelligence Learning Design - Gunawan, Dani; Musthafa, Bachrudin; Wahyudin, Dinn (SCAD Independent, 2022)
This research aimed to determine the difference in students' language skills levels before and after using a verbal-linguistic intelligence-based learning design. This research was conducted in an elementary school in Garut Regency, Indonesia, using a pre-experimental design with a one-group pretest-posttest design. The participants were 22 sixth-grade elementary school students. The data were obtained by test. The test instrument was tested for validity and reliability. Then, the data were analyzed by inferential and descriptive tests. The inferential test was done through normality and homogeneity tests. Furthermore, the data were tested for the mean difference using SPSS 22 software. The results prove differences in students' language skills before and after applying the verbal-linguistic intelligence-based learning design. The acquisition sees the difference in scores of the average score of each skill after treatment increases with an n-gain score of 68.75. This proves that verbal-linguistic intelligence-based learning design can improve each student's language skills. The findings can be an insight for future researchers conducting research on learning design based on verbal-linguistic intelligence or language skills.